The challenges of implementing inclusive education programs in outermost, frontline, and Underdeveloped areas - Djulaiha Sukmana; Icuk Muhammad Sakir; Eka Nurwahyuliningsih; Yolandika Arsyad (STKIP Singkawang, 2025)
The government has initiated an inclusive education program as an effort to enhance educational equality for children with special needs who experience physical, mental, and social limitations. This policy is regulated under Law No. 20 of 2003 concerning the National Education System and further elaborated in Ministerial Regulation No. 70 of 2009 on Inclusive Education, where inclusive education is defined as an educational system designed for children with special needs and/or children with special talents so they can learn together with other students in regular schools. Inclusive education has been implemented nationwide, including in Outermost, Frontline, and Underdeveloped Areas (3T), although challenges persist in fully implementing inclusive education in schools. This study aims to describe the challenges faced by educational institutions in implementing inclusive education in 3T areas. The research employs a literature review method by analyzing 25 academic articles related to the primary topic of inclusive education, sourced from Google Scholar, Research Gate, Elsevier, and several books. Based on the reviewed studies, challenges in implementing inclusive education in Indonesia, especially in 3T areas, include: teachers' insufficient qualifications, making it difficult to provide the best services for children with special needs; a curriculum that is not flexible enough to meet children with special needs, causing difficulties in understanding learning materials; inadequate facilities and infrastructure; and limited support from parents, communities, and the government in the implementation of inclusive education. To achieve effective inclusive education, collaboration, commitment, and concrete efforts from all stakeholders are necessary to ensure children with special needs receive equal educational opportunities.